2008
DOI: 10.1016/j.jsbmb.2008.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Human prostate stromal cells stimulate increased PSA production in DHEA-treated prostate cancer epithelial cells

Abstract: Dehydroepiandrosterone (DHEA) is commonly used as a dietary supplement and may affect prostate pathophysiology when metabolized to androgens and/or estrogens. Human prostate LAPC-4 cancer cells with a wild type androgen receptor (AR), were treated with DHEA, androgens (DHT, T, or R1881), and E 2 and assayed for PSA protein and gene expression. In LAPC-4 monocultures, DHEA and E 2 induced little or no increase in PSA protein or mRNA expression compared to androgentreated cells. When prostate cancer-associated (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 40 publications
4
37
0
Order By: Relevance
“…However, coculture with stromal cells, especially PCaSCs, strongly activated PSA promoter activity induced by DHEA. Although our results are consistent with Arnold et al (2008) observation that testosterone synthesized from DHEA in PCa-derived stromal cells contributed to PSA induction in LAPC4, we extended these studies further to elucidate which pathways were involved in testosterone synthesis. Specifically, we identified that the increased level of DHEAinduced AR activity by stromal cells was dependent on the synthesized level of testosterone and DHT achieved by coculture.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, coculture with stromal cells, especially PCaSCs, strongly activated PSA promoter activity induced by DHEA. Although our results are consistent with Arnold et al (2008) observation that testosterone synthesized from DHEA in PCa-derived stromal cells contributed to PSA induction in LAPC4, we extended these studies further to elucidate which pathways were involved in testosterone synthesis. Specifically, we identified that the increased level of DHEAinduced AR activity by stromal cells was dependent on the synthesized level of testosterone and DHT achieved by coculture.…”
Section: Discussionsupporting
confidence: 89%
“…This activity could readily contribute to androgen deprivation-refractory PCa after ADT. Recently, Arnold et al (2008) have described a similar study using coculture of LAPC4 androgen-sensitive PCa cells with stromal cells. According to their study, PCa-derived stromal cells also increased PSA mRNA expression induced by DHEA.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that this study showed no association of vitamin intake with increased PSA, vitamin use might increase the risk of prostate cancer without elevation of serum PSA. Although DHEA exerts minimal effects on normal prostate, in cancer-associated tissues a reactive stromal microenvironment can promote prostate proliferation or PSA production in the presence of DHEA (Arnold et al, 2008). Although many kinds of nutritional supplements are increasingly consumed for their anti-aging effects, their effectiveness and long-term safety for prostate tissues are uncertain and rather risky.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Many research groups have also shown that a dynamic stromal-epithelial interaction plays a critical role in the progression and metastasis of PCa. [14][15][16][17][18][19][20] Growth factors play a central role in mediating the interactions between epithelial and stromal cells. 21 The stromal-epithelial interaction is also critical for mediating the effects of these molecules on epithelial cells.…”
Section: Introductionmentioning
confidence: 99%